MANAGING THE EFFECTIVENESS OF AN ENTERPRISE’S OPERATIONS SYSTEM IN OPERATIONS MANAGEMENT - KAPINOS, Hennadii; LARIONOVA, Katerina (Herald of Khmelnytskyi National University. Economic sciences, 2025)
This article examines the theoretical and practical aspects of managing the effectiveness of an enterprise’s operational system in the context of modern operations management. The operational system is considered as an integrated complex that transforms resources into final products or services and has a decisive impact on business competitiveness and sustainability. Key factors affecting its efficiency are identified, and methods for optimizing operational processes are proposed. Conceptual foundations for managing the effectiveness of an enterprise’s operational system have been developed based on a comprehensive systems approach. This approach includes analysis of essential characteristics, theoretical substantiation, identification of subjects and objectives, determination of functional content, and development of methodological tools for efficiency assessment. The study examines the approach to managing the efficiency of activity as a system that takes into account modern business environment challenges and ensures adaptability to changing market conditions. The following tasks were accomplished: systematization of approaches to evaluating operational systems’ effectiveness, identification of key internal and external influencing factors in the context of digital transformation, and development of an integrated approach to performance management. Additionally, methods for managing the effectiveness of an enterprise’s operational system were systematized across different management levels (strategic, current, and operational). The research proposes an implementation mechanism for managing the effectiveness of an enterprise’s operational system, with a model that includes formation and functioning subsystems. Significant attention is given to the functioning subsystem, which includes strategic analysis, operational strategy development, implementation of transformational measures, current state diagnostics, formation of operational budgets, and monitoring of indicators. Special attention is paid to efficiency assessment through a system of key performance indicators (KPI). The research results aim to improve the theoretical foundations of operations management and develop practical recommendations for enhancing the efficiency of enterprise operational systems. This will ensure their sustainability and competitiveness in the long term.